2018
DOI: 10.1590/1678-4685-gmb-2017-0194
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of deafness and renal abnormalities in HDR syndrome caused by a de novo mutation in the GATA3 gene

Abstract: HDR syndrome is a rare autosomal dominant disorder caused by mutations in the GATA3 gene and characterized by hypoparathyroidism, sensorineural deafness and renal abnormalities. Here we report a Brazilian family, from which the proband, his mother and his grandfather were diagnosed with bilateral sensorineural hearing loss. Molecular screening of the GJB2, GJB6 and MTRNR1 genes in the proband showed no alterations; however, whole exome sequencing detected a heterozygous mutation, c.1099C > T (p.Arg367*), in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…; Martins et al . ). Heterozygous null gata3 mice ( gata +/− ) have a complex cochlear pathology, including OHC degeneration as early as 1 month of age, followed by loss of pillar cells, IHCs and nerve fibres (van der Wees et al .…”
Section: Introductionmentioning
confidence: 97%
“…; Martins et al . ). Heterozygous null gata3 mice ( gata +/− ) have a complex cochlear pathology, including OHC degeneration as early as 1 month of age, followed by loss of pillar cells, IHCs and nerve fibres (van der Wees et al .…”
Section: Introductionmentioning
confidence: 97%
“…Further studies have provided evidence that GATA3 is also crucial for the coordinated maturation of sensory hair cells and their innervation ( Bardhan et al, 2019 ). In humans, the expression of GATA3 is localized to the cochlear duct and the spiral ganglion between weeks 8 and 12 of gestation ( Roccio et al, 2018 ); the loss of GATA3 in inner hair cells leads to hearing loss and accounts for some of the deafness connected to hypoparathyroidism and renal anomaly (HDR) syndrome ( Van Esch et al, 2000 ; Martins et al, 2018 ). Researchers have also demonstrated that GATA3 plays critical roles in neural crest cell development and neuronal differentiation in some cranial neural crest derivatives ( George et al, 1994 ; Lieuw et al, 1997 ; Lakshmanan et al, 1999 ).…”
Section: Discussionmentioning
confidence: 99%